PERAN PENYULUH TERHADAP PEMANFAATAN PENGERING DRYER ULTRAVIOLET PADA USAHATANI JAGUNG DI DESA MONGIILO UTARA KECAMATAN BULANGO ULU KABUPATEN BONE BOLANGO (The Role Of Extension Workers On Utilization Ultraviolet Dryer Dryer In Corn Farming In North Mongiilo Village, Bulango Ulu District, Bone Bolango Regency) - RAHMA, PUTRI; BARUWADI, MAHLUDIN H.; ADAM, ECHAN (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2023)
The aim of the study was to identify the characteristics of farmers using ultraviolet dryers and to find out the role of extension workers in the use of ultraviolet dryers in corn farming in Mongiilo Utara Village, Bulango Ulu District, Bone Bolango Regency. The research method is descriptive with a survey method with the main data collection through a questionnaire on 45 farmers as the research sample. The results showed the characteristics of farmers using ultraviolet dryers on corn farming in Mongiilo Utara Village, Bulango Ulu District, Bone Bolango Regency. The majority of farmers are men (97.8%) with a dominant age of 20-55 years (84.4%). The education level of the majority is elementary school (88.9%) and the number of family dependents is 1-2 people (51.1%). Extension officers have an important role as motivators, consultants, educators, and facilitators in utilizing ultraviolet dryers. The aim is to introduce the technology, provide guidance, increase understanding and skills of farmers, and help overcome barriers to the use of tools. With this role, it is hoped that farmers can optimize the use of tools and increase production and income.